MEPROCS framework for Craniofacial Superimposition: Validation study. (November 2016) - Ibáñez, O.; Vicente, R.; Navega, D.; Campomanes-Álvarez, C.; Cattaneo, C.; Jankauskas, R.; Huete, M.I.; Navarro, F.; Hardiman, R.; Ruiz, E.; Imaizumi, K.; Cavalli, F.; et al.
Highlights: Quantitative and qualitative validation of the Craniofacial Superimposition framework developed in MEPROCS. Multi-parametric analysis according to framework understanding and fulfilment, participants' performance, and correlation. Those who follow the MEPROCS recommendations improve their performance. Abstract: Craniofacial Superimposition (CFS) involves the process of overlaying a skull with a number of ante-mortem images of an individual and the analysis of their morphological correspondence. The lack of unified working protocols and the absence of commonly accepted standards, led to contradictory consensus regarding its reliability. One of the more important aims of 'New Methodologies and Protocols of Forensic Identification by Craniofacial Superimposition (MEPROCS)' project was to propose a common framework for CFS, what can be considered the first international standard in the field. The framework aimed to serve as a roadmap for avoiding particular assumptions that could bias the process. At the same time, it provides some empirical support to certain practices, technological means, and morphological criteria expected to facilitate the application of the CFS task and to improve its reliability. In order to confirm the utility and potential benefits of the framework use, there is a need to empirically evaluate it in CFS identification scenarios as close as possible to the reality. Thus, the purpose of this study is to validate the CFS framework developed. For that aim 12 participants were asked to report about a variable number of CFS following all the recommendations of the framework. The results are analysed and discussed according to the framework understanding and fulfilment, the participants' performance, and the correlation between expected decisions and those given by the participants. In view of the quantitative results and qualitative examination criteria we can conclude that those who follow the MEPROCS recommendations improve their performance.